METODE RIWAYAT BI AL-MAâ€˜NÃ¢ DAN HADIS POPULER DI INDONESIA: STUDI HADIS-HADIS MAULID RASULULLAH - Akmaluddin, Muhammad (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2017)
Peripheral areas such as Indonesia are in necessity to have more understanding of hadith content (matn) than on knowledge of hadith in its complexity. The long distance of knowledge dissemination, development and codification of hadith period in Indonesia, than in the Arabian Peninsula, caused many scholars to prioritize hadith studies in its understandable form, which is more practical, than in its theoretical one. Based on the study of hadith of maulid nabi (prophet?s birthday) in Indonesia, it strongly suggests that understanding and practicing hadith are more important than studying of hadith knowledge. Popular hadith of maulid consists of several hadiths and several comments (sharh). Those hadiths are then compiled and summarized to be one simple sentence. This sentence is then considered as hadith, and people could be easily understand and memorize it. The same method is also applied in the writing and teaching of hadith books. This compilation and summary seem to be an inverted proof of isnâd-cum-matn, which argues that the transmission of hadith is an ongoing process of oral words along the times.